Sepsis in Respiratory Diseases: A Narrative Review - Viswanathan, Vinod Kumar (British Journal of Healthcare and Medical Research, 2026)
Objective: To review the epidemiology, clinical spectrum, and management of sepsis in respiratory diseases, with emphasis on implications for clinical practice. Design: Narrative review. Data sources: PubMed, Google Scholar, and international guideline documents including the Surviving Sepsis Campaign. Eligibility criteria: English-language studies, reviews, and guidelines addressing adult sepsis and respiratory infections. Results: Respiratory infections are the leading source of sepsis and are associated with the highest mortality. Patients with pneumonia, chronic obstructive pulmonary disease, Tuberculosis, interstitial lung disease, and malignancy are at particularly high risk. Early identification and prompt implementation of evidence-based management bundles are associated with improved outcomes. Conclusions: Sepsis remains a major contributor to mortality among patients with respiratory diseases. Standardised recognition, timely management, and preventive strategies are essential to improve outcomes.